Work experiences of Nurse Academics: A qualitative study. (November 2021) - Singh, Charanjit; Jackson, Debra; Munro, Ian; Cross, Wendy
Abstract: Background: The evidence suggests that heavy workloads, pressure to publish, lack of recognition and job insecurity has led to increased job stress among nurse academics. Lack of proper mentoring, reorientation and transition into an academic role are contributory factors towards the lack of retention and recruitment among nurse academics. Internationally, the sustainability of the nurse academic workforce is an area of great concern. The experiences of nurse academics have not been extensively investigated. Objectives: To explore the work experiences of nurse academics. Design: Qualitative Exploratory study. Data were analysed using thematic analysis. Participants: A purposive sample of nurse academics ( n  = 19), recruited from all states and territories of Australia, lecturer to professor level and work experiences from 2 to 30 years. Methods: Data were collected using semi-structured face to face and telephone interviews. Data were transcribed verbatim and thematically analysed based upon Braun & Clark's model. The study is reported in accordance with the COREQ guidelines. Ethical approval was granted by the relevant University Human Research Ethics Committee. Results: Four main themes were identified (a) Helping students achieve, finding satisfaction through student engagement, (b) working with challenging students, (c) increased workloads, lack of support and resources and (d) difficulty with retention of newly appointed staff. Conclusions: Although the findings highlighted the interactions with nursing students were a positive experience, many of the participants raised great concern about the challenging, difficult, academically weak, rude, and manipulative students. The growing workload increased non-academic administrative work, and the inability to sustain newly appointed staff were areas of great concern. Doing more with less and not being recognized were pertinent factors that needed to be addressed.